CONTRIBUTION TO THE STUDY OF CARCINONEMERTES FROM THE COAST OF MEXICO - RIOJA, ENRIQUE (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
In a series of 102 human diaphragms, examined by direct examination rather than digestion methods, Trichinella was found in only one case
ANS INST BIOL
Keywords: CONTRIBUTION, STUDY, CARCINONEMERTES, COAST OF MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL